APPLICATION OF POWTOON-BASED AI TECHNOLOGY IN MAKING ENTREPRENEURSHIP TEACHING MATERIALS - Fangki; Mustakim, Nuhriyan; Anisah, Aan; Febianti, Yopi Nisa (EDUCATIONE, 2024)
Technological advances with various other implications also require a greater role for the world of education, especially for teachers who use different technologies, methods and approaches in conveying material and values ​​to students. A teacher's ability to adapt to technological developments has become an inevitability that cannot be avoided. Based on the research obtained, the results show that the development of powtoon learning media has a feasibility percentage of 83,75% (feasible). Student learning outcomes were proven to have increased in obtaining a minimum score of 70 and a maximum score of 100. The gain test showed that 18 students obtained high score criteria and 9 students obtained medium score criteria. In the student response questionnaire, the percentage was 93.4% (Very Eligible). Thus, it can be stated that the Powtoon learning media is suitable for use in entrepreneurship learning. It is hoped that this research can help students and the instruments involved in the process of teaching and learning activities.